Neutrality and the Social Contract - Carroll, Ian (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2009)
Given the fact of moral disagreement, theories of state neutrality which rely on moral premises will have limited application, in that they will fail to motivate anyone who rejects the moral premises on which they are based. By contrast, contractarian theories can be consistent with moral scepticism, and can therefore avoid this limitation. In this paper, I construct a contractarian model which I claim is sceptically consistent and includes a principle of state neutrality as a necessary condition. The principle of neutrality which I derive incorporates two conceptions of neutrality (consequential neutrality and justificatory neutrality) which have usually been thought of as distinct and incompatible. I argue that contractarianism gives us a unified account of these conceptions. Ultimately, the conclusion that neutrality can be derived without violating the constraint established by moral scepticism turns out to rely on an assumption of equal precontractual bargaining power. I do not attempt to defend this assumption here. If the assumption cannot be defended in a sceptically consistent fashion, then the argument for neutrality given here is claimed to be morally minimal, rather than fully consistent with moral scepticism.